Human life cost in anaesthesiology cost-benefit decisions - Naftalovich, Rotem; Iskander, Andrew J.; Naftalovich, Daniel; D. Eloy, Jean; J. Discepola, Patrick; L. Tewfik, George; Chaudhry, Faraz; Rodriguez-Correa, Daniel (Anestezjologia Intensywna Terapia, 2021)
The United States (US) aviation industry provides a potentially useful mental model for dealing with certain cost-benefit decisions in aesthesiology. The Federal Aviation Administration (FAA), the national aviation authority of the United States, quantifies a price for the value of a human life based on the U.S. Department of Transportation’s (DOT) value of a statistical life (VSL) unit. The current VSL is around $9.6 million, indexed to grow with consideration given to inflation and wage changes from the 2016 baseline of $9.4 million [1]. To illustrate the concept, if the FAA estimates that 100 people are likely to die in the future given the current practice standards then the monetary cost of this loss will be $940 million. The FAA uses this estimated monetary value as an official reference point in its regulatory decisions, and the agency publishes in detail how it derives the estimated value. When proposing new regulations, the FAA bases its decisions on comparisons of the human life cost associated with the existing regulation versus the alternative cost that the industry stakeholders will incur subsequent to the adoption of the regulation. In this example, if the cost incurred by the industry is more than the $940 million cost then the FAA will not adopt the proposed regulation and hence will not require the industry to undertake this cost.